(untitled) (Práxis Educativa, 2018)
The developed study required parameters of objectification for the construction of the epistemic-practical space of Education Policy in the Post-Graduate Programs in Education of the Northeast region of Brazil. Statistical instruments were used, such as the descriptive analysis and factor analysis of multiple correspondence - whose objective was to highlight and, at the same time, to delimit the different kinds of capital acting in the space of social production of knowledge, through capital properties (or positional attributes) extracted from the Lattes Platform of CNPq. In fact, it became necessary to recognize the historically situated academic elite as holders of specific values and with socially defined interests in the scientific field of Education Policy. The discussion converges to an analysis about the social and practical determinants of the agents that produce academic representations in this field, since it is necessary to explore the logic of competitive struggles and the battles that take place around the game to impose the production agenda, understood as agents’ positions taken in relation to their universe of social practices. Keywords: Academic elite. Scientific field. Education policy. Analysis of correspondence. Northeast Region.